Targeting Serotonin Transporters in the Treatment of Juvenile and Adolescent Depression - Bowman, Melodi A.; Daws, Lynette C. (Frontiers in Neuroscience, 2019)
Depression is a serious public health concern. Many patients are not effectively treated, but in children and adolescents this problem is compounded by limited pharmaceutical options. Currently, the Food and Drug Administration approves only two antidepressants for use in these young populations. Both are selective serotonin reuptake inhibitors (SSRIs). Compounding matters further, they are therapeutically less efficacious in children and adolescents than in adults. Here we review clinical and preclinical literature describing the antidepressant efficacy of SSRIs in juveniles and adolescents. Since the high-affinity serotonin transporter (SERT) is the primary target of SSRIs, we then synthesize these reports with studies of SERT expression/function during juvenile and adolescent periods. Preclinical literature reveals some striking parallels with clinical studies, primary among them is that, like humans, juvenile and adolescent rodents show reduced antidepressant-like responses to SSRIs. These findings underscore the utility of preclinical assays designed to screen drugs for antidepressant efficacy across ages. There is general agreement that SERT expression/function is lower in juveniles and adolescents than in adults. It is well established that chronic SSRI treatment decreases SERT expression/function in adults, but strikingly, SERT expression/function in adolescents is increased following chronic treatment with SSRIs. Finally, we discuss a putative role for organic cation transporters and/or plasma membrane monoamine transporter in serotonergic homeostasis in juveniles and adolescents. Taken together, fundamental differences in SERT, and putatively in other transporters capable of serotonin clearance, may provide a mechanistic basis for the relative inefficiency of SSRIs to treat pediatric depression, relative to adults.